THE USE OF ADJUSTED READING MATERIALS IN THE TEACHING OF READINGCOMPREHENSION - SANTYARINI, RESTU (RETAIN : Journal of Research in English Language Teaching, 2013)
Adjusted Reading Materials for Reading Comprehension 1 THE USE OF ADJUSTED READING MATERIALS IN THE TEACHING OF READING COMPREHENSION Restu Santyarini 092084013 English Education, Faculty of Language and Art, State University of Surabaya restubelle.santya@gmail.com Dosen Pembimbing: Prof. Dr. Susanto, M. Pd. English Department, Faculty of Language and Art, State University of Surabaya Abstrak Penggunaan materi yang terlalu sulit oleh guru ketika mengajar reading menjadi alasan kenapa siswa tidak dapat memahami teks dengan baik. Mereka menemukan banyak kesulitan ketika membaca teks naratif yang diberikan. Guru harus merivisi RPP sebelumnya dengan memilih materi yang disesuaikan yang sejalan dengan kemampuan, kebutuhan dan ketertarikan siswa. Riset ini merupakan penelitian tindakan kelas yang hanya terdiri dari satu siklus. Ini disebabkan karena hasil pembelajaran menunjukkan bahwa tujuan pembelajaran telah dicapai. Riset ini diadakan di kelas VIII di salah satu SMP di Ngawi. Peneliti melakukan kolaborasi dengan guru dalam melaksanakan proses belajar mengajar. Peneliti menggunakan catatan lapangan tidak terstruktur untuk mengumpulkan data. Data harus dipilah dan diklasifikasikan menjadi data yang relevan dan tidak relevan. Kemudian data yang relevan akan diklasifikasikan dan dianalisis berdasarkan rumusan masalah. Hasil pengamatan menunjukkan bahwa penggunaan materi membaca yang sesuai membantu siswa untuk mengkategorisasikan teks naratif berdasarkan strukturnya, mengidentifikasi pesan moral dari teks naratif, menjawab pertanyaan seputar teks naratif dan menyimpulkan teks naratif. Kata Kunci: Penggunaan, Materi Membaca yang Sesuai, Pemahaman Membaca Abstract The use of difficult narrative materials by the teacher in the teaching reading seems to be the reason why the students cannot comprehend the text well. They found many difficulties in reading the narrative text given. The teacher should revise the previous lesson plan by choosing the adjusted reading materials which in accordance with the students’ ability, need and interest. This research is a classroom action research with one cycle only. It was because the result of the study indicated that the goals of the study have been accomplished. This research was conducted at class VIII in one of junior high school in Ngawi. The researcher made collaboration with the teacher in conducting the teaching and learning process. The researcher used unstructured field notes to collect the data. The data had to be sorted and classified to choose the relevant data and un-relevant data. Then the relevant data will be classified and analyzed based on the research questions. The result of the observation indicated that the use of adjusted reading material in the revised lesson plan helped the students in categorizing the narrative text based on its generic structure, identifying the moral value of the narrative text, answering the question of the narrative text as well as inferring the narrative text. Keywords: The use, Adjusted Reading Material, Reading Comprehension. INTRODUCTION Background of Study Students’ comprehension is the ultimate goal for the students when they do learn reading skill. It is the process of the readers to construct the meaning of the text they read. Iwai (2010) states reading comprehension is based on using the appropriate meaning-making processes from the printed messages. From Iwai’s statement it could be indicated that reading comprehension involves the passage, the reader, and the context. The readers construct meanings of the passage using their background knowledge, analyzing words, inferring the text, and identifying key vocabulary or information. From those explanations it could be concluded that reading comprehension needs readers’ thinking and reasoning in order to does it well. Since they must activate what they have known to build the meaning of the passage without knowing the meaning of each word. They relate their knowledge and the context of the passage to build the meaning of whole. Ejournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216 In one of small towns in East Java, there is a junior high school which locates in the edge of big road of Surabaya-Solo. Because of its location, this school is very crowded. The teaching of English lesson in this school is conducted two times a week. One of the classes in this school is the eighth grade of C which consists of 25 students, 14 females and 11 males. The class is large enough for teaching and learning process. This class is not completed with an AC, a LCD projector, as well as a speaker. The students have arranged the chairs and tables well in order to make them study easily. They mix their seats so that the clever students will spread with the low and medium students. When the teacher taught the basic competence 11.3 which about responding the meaning and rhetorical action of a short simple essay accurately, fluently and in the context of everyday life in the form of recount and narrative, she gave a narrative text to them, then she asked them to comprehend the text. The teacher used clear and loud voice during teaching learning process; however it was not enough to make the students understand the text well. Besides the fact indicates that in the process of the teacher guiding them to comprehend the text, there were several students who felt difficult to understand the text. Although there were some students who actively guessed the meaning of the text, there were more students who were silent or talking to their friends. It made them cannot complete the task well. The teacher used three-phase technique, speech, questions-answers and task gift to teach reading. It seemed to be boring activities for the students because they had less opportunity to take part in the learning process. At that time, the teacher explained about narrative text. However the narrative texts given to the students were very difficult for them. It was very confusing the students. The text used by the teacher was out of their capability. They had to depend on the dictionary to know the meaning of words. It seemed to be boring for them. As the result, they stopped finding the meaning in the dictionary and started talking to others. It was one of the reasons why the students found difficulties during reading class. They spent most of their time to find the meaning of the words than understand what the text talk about. In other cases, there were some parts of the lesson plan that needed to be revised. It included the indicators and learning objectives. The indicators in the lesson plan were not specific enough. She only stated the students could identify the information, the aim and the language features of the functional text. How the students would identify this kind of text without knowing what the text is. Besides, the objectives of study she designed were not based on the indicators. It seemed that they were from different part. It was important for her to design the objectives of the study from the indicators. So she could measure whether the indicators have been reached by the students or not by looking to the objectives of the study. Furthermore, learning activities of the lesson plan were only teacher activities. There had to be students’ activities too since in the teaching learning process the main actors are the students. The teacher is only the assistant who will help them when they find difficulties. Whereas the assessment in the lesson plan was only product assessment, there was no process assessment. In the teaching and learning activities, the most important thing was in the process. It was not only the students’ result that could be used as the measurement of the successful learning. It also could be seen from the process. It was the reason why process assessment was very needed to be stated in the lesson plan. The revised lesson plan was given to the teacher as the solution to the problem faced by her. Choosing the adjusted reading material for the students was the important thing to do. It should be easier material that could help them to understand what narrative actually is. It should be familiar to them so that they could comprehend it well. It also included formulating more specific indicators based on the basic competence, adjusting the learning objectives to the indicators, designing the learning activities which will encourage students to participate as well as doing the process assessment correctly. The new learning activities were divided into 2 tasks. The first task was applying pair work. The students were asked to work in pair, then they got a narrative from the teacher and their job was to comprehend the text given. The second was applying Quiz. To do quiz, the teacher divided the class into two big groups. Every group got a text. Then the member of each group made a question to be asked to the opposite team. The team that could get biggest was the winner. During the quiz was running, the teacher was being the moderator of the two groups. The students can be called as successful readers when they can comprehend all the component of the text. They know what the text about. They are capable to answer the questions related to the text (the explicit meaning) as well as differentiate connotation and implicit meaning of the text. From the rational above, it was necessary to conduct a research of the used of the appropriate material in teaching reading comprehension. How do the students respond toward the use of appropriate material in the teaching of reading comprehension? This study focused on how the students categorize the narrative text based on its generic structure, how the students identify the moral value of the narrative text, how the students answer when they get questions from the teacher and how the students make inferences while reading the narrative text. Review Literature The ultimate goal of learning a language is to be able to comprehend and produce it in unrehearsed situation, which demands both receptive and productive creativity (Brown: 2000). Based on that statement, we know that someone can be said learning a language if he/she can use it in every situation. However in the reading process, they do not only extract the meaning of every word but also connect the information they have got from the text with their own prior knowledge. Pang, Muaka, Bernhardt, & Kamil (2003) state reading is a complex activity that involves both perception and thought. From their statement we know that the readers’ knowledge also play a role to help them understand the text more. They have had prior knowledge in the form of Adjusted Reading Materials for Reading Comprehension 3 perception. It is about what they have known. It may be related to the new information stated in the text. Then they will start to think in order to get the meaning from written text they read. It may make them understand the text easier. Based on those explanations, the writer concludes that reading is an active activity of seeking the information stated on the text and relating to their own prior knowledge. Reading comprehension is the ability to understand a written passage of text. It allows readers to interact with the text in a meaningful way. It is the bridge from passive reading to active reading. Active readers will not read from letters and words but from characters and contexts. For many, it also unlocks the door to a lifetime of reading recreation and enjoyment. Supporting to that, Pardo (2004) says that comprehension is a process in which readers construct meaning by interacting with the text through the combination of prior knowledge and previous experience, information in the text, and the stance the reader takes in relationship to the text. Before reading a text, readers have their own knowledge. In the process of comprehending, this knowledge will be very useful for them. The combination of readers’ prior knowledge and text’s information will be a great factor to build meaning of the text. The goal of teaching reading comprehension strategies is to give readers the tools which they need to be effective readers and independent learners (Moreillon: 2007). Reading itself is not an activity of getting fixed meaning from written texts. The readers may use their prior knowledge to support them in understanding the text. In the process of reading, sometimes readers do not only get a text with familiar words but also a text with unfamiliar words. They is not necessarily to read and understand the meaning of every word. They only need to find the main idea of the text so that they can make a summarize about it. The material that should be taught in reading lesson must be in accordance with the students’ interests and backgrounds. In spite of it all, the teacher should also consider the applicable curriculum. According to the prevailing curriculum, the material to be taught is a narrative text. So here the teacher should present the narrative text that can attract students as well as not contrary to the background of the students. This will make the students more interested in reading activities. Iwai (2007) states the teacher needs to be aware in how the students relate their prior knowledge and interact with a text critically, so that it guides them to have deeper understanding of texts and to become more powerful readers in other types of reading materials. Basically the more the students know about the material they are going to read, the more successful readers they will be. It is because they do not need to struggle to comprehend the texts. Only by reading the title, they will know what will happen next. It is the way where their prior knowledge takes role most. There are some studies which are conducted in the implementation of fun reading comprehension teaching. The recent study was done by Akgün (1997) which concludes that the teacher must try to use fun activities in the classes before she makes the necessary changes according to the specific needs and attitudes of your own students. Other study was done by Raman (2004). It concludes that using reading quiz in the reading class is one way of motivating students to read and sustaining their interest in reading. The followings are the steps of teaching reading comprehension adapted from Valette & Disick (1972) and Brown (2000). They can be done in the teaching reading comprehension using adjusted reading materials. The first step to do is pre-reading activities. Here, the teacher finds an interesting passage, which may appeal to most of your students. By doing that, the teacher tries to activate the students’ prior knowledge. Besides, the teacher needs to introduce the topic of the passage, encourage skimming, scanning, and predicting. The students can bring the best of their knowledge and skills to a passage when they can relieve to it. They will feel less unpleasant to the reading activities because they have already been familiar with the passage which is using their daily topics. The ultimate goal of reading is comprehension, so in the second stage the teacher needs to direct the students to that goal. It can be adapted from Raman (2004) who used quiz for his teaching of reading comprehension. It can present fun while-reading activities. METHODOLOGY Research Design The design of this research is classroom action research. According to Susanto (2007) classroom action research is a research about the implementation of teaching and learning process in the classroom. It is conducted to improve the quality of education by evaluating the previous unsuccessful study. It must be a problem why the study is unsuccessful. It means that the problem of the research comes from the classroom itself. Wallace (1998) also explains that action research is different with other researchs in that it nearly always arises from some spesific problem or issue arissing out of usual practice. Therefore it focuses in the problem in its approach and practices in its intended outcomes. Those explanantions give clear descriptions why in doing this research the researcher needs to collaborate with the teacher of the class. They become partners for this study. It is because the teacher is someone who knows the students’ ability and behavior in the class. Setting of the Study The setting of the study was class VIII of SMP Negeri 2 Geneng. The researcher chose this class because based on the teacher’s information this class had problems in the teaching and learning process. This class consists of 25 students, 14 females and 11 males. It is large enough for teaching and learning process. It is not completed with an AC, a LCD projector, as well as a speaker. The students have arranged the chairs and tables well in order Ejournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216 to make them study easily. They mix their seats so that the clever students will spread with the low and medium students. It is purposed to make the class go smoothly. It seems not to work because several students feel difficult to comprehend the narrative text given by the teacher. Although there are some students who actively guess the meaning of the text, there are more students who are silent or talking to their friends. It make them cannot complete the task well and the class be crowded. Research Procedures This classroom action research has some steps. According to Susanto (2007), those steps are planning, implementation, observation and reflection in the field and reflection stage. 1. Planning Stage In this stage, the researcher looked for someone who could be a partner of this research. This partner had to be a teacher. She is needed as the requirement of Classroom Action Research that is collaborative and classroom-based. The teacher explained her problem during the learning process. This problem was identified and evaluated by the researcher and the teacher. Then they formulated the research problem in order to be solved by using classroom action research. They prepared all the things which were used during the learning process. It consisted of reformulating the new lesson plan. It concerned with the learning materials which were used by the teacher. After making the revised lesson plan, the researcher and the teacher set the criteria of the study. These criteria were in line with research questions of the study. They were used to measure the students’ comprehension. The following are the criteria of the study 1. The first criterion was based on the first research question, “1.2.1. To what extent are the students able to categorize the narrative text based on its generic structure?”. It means that the ultimate goal of the students learning was the students were able to categorize the narrative text based on its generic structures. The text used for the first criterion was Snow White. Students were required to categorize the text of Snow White given by the teacher. The students were considered to be able to meet the target of the first research question if 75% of the number of students (22 students) was able to categorize narrative text based on its generic structure correctly; that is orientation, complication and resolution. 2. The second criterion was according to the second research question, “1.2.2. To what extent are the students able to identify the moral value of the narrative text?”. The goal of the study was the students could identify the moral value of the narrative text. Here, the researcher used two different texts, Mantu’s Little Elephant and The Goose That Laid Golden Eggs. The reason why the researcher used two texts was because in the process of learning, the teacher asked the students to make two big groups. Each group got a text. The students were considered to be able to meet the target of the second research question if 75% of the number of students (22 students) was able to identify the moral value of the narrative text correctly. 3. The third criterion was based on the third research question, “1.2.3. To what extent are the students able to answer the questions about the narrative text given by the teacher?”. The result to be achieved was the students were able to answer the questions about the given text. Here, the researcher used the same text as the text used in the second criterion because the second and third criteria would be achieved by students in the same task, which was playing quiz. But in this third criterion, students were stated being successful not only from their ability to answer questions, but also on their ability to ask questions. Students were considered to meet the target of the third research question if 75% of the number of members of each group (11 students in each group) was able to ask questions and also answer questions about the two texts properly. 4. The fourth criterion was according to the fourth research question, “1.2.4. To what extent are the students able to make inferences while reading the narrative text given by the teacher?”. For the fourth criterion, the researcher used the same text as the first criterion that was Snow White. This was because the first and the fourth criteria were done in the same task. Teacher asked students to work in pairs. Then they had to infer what they read as a single group. The students were considered to be able to fulfill the fourth research question if 75% of the number of the students (22 students) was able to infer the narrative text given by the teacher. In the revised lesson plan, the researcher designed the meeting into two. In the first meeting, the teacher gave two narrative texts to the students that were Malin Kundang and Snow White. Malin Kundang was used to explain the concept of narrative text to the students. After explaining, the teacher asked the students to work in pair to discuss the text of Snow White. While in the second meeting, the teacher gave two other texts to the students, Mantu’s Little Elephant and The Goose That Laid Golden Eggs. They were asked to make a class work then they had to make questions about Adjusted Reading Materials for Reading Comprehension 5 the text and asked them to their opposite group. In conclusion the researcher set the revised lesson plan with two tasks of four different narrative texts in two meetings. The researcher and the teacher also prepared field notes to write all information and everything happened during teaching learning process. So it could be concluded that this stage was the stage where they made a new scenario of the teaching process. 2. Implementation Stage It was the stage where the new scenario of the teaching process was implemented. Here, the teacher taught as she did regularly. She taught based on the revised lesson plan which was formulated in the planning stage. This stage was held in two meeting. The first meeting was used by the teacher to explain about the concept of narrative. Example 1. Descriptive Note Catatan Deskriptif: Guru kemudian menunjukkan slide yang sudah disiapkan, Didalam slide dijelaskan apa itu teks naratif, generic structure, tujuan komunikatif dan struktur kebahasaan dari teks naratif sekaligus sebuah contoh teks naratif. Contoh yang diberikan adalah cerita Malin Kundang. Selama menampilkan slide, guru juga memberikan pertanyaan kepada siswanya mengenai apa yang ada di dalam slide. Guru : “Okay students, pay attention to these slides please. Here, you can see that narrative text is the text for … Siswa : “Entertaining the readers” (serentak) Guru : “Good students. So if you want to be entertained, you can read narrative text. What about its generic structure? Let’s go to the next slide. It consists of the first, orientation. It is about the opening paragraph where the characters of the story are introduced. The second is complication. It is the part where the problems in the story developed. The third or the last is resolution. What is resolution? Anyone knows what is it? ……. Here, the teacher ensured that all the students have good understanding of narrative text before they went to the next activity. The second meeting was used to employ quiz. Example 2. Descriptive Note Catatan Deskriptif: Guru menjelaskan apa yang akan dilakukan hari ini. Mereka akan mengadakan kuis. kemudian guru menjelaskan cara memainkannya. Siswa mendengarkan dengan seksama penjelasan yang diberikan oleh guru. Salah satu siswa mengajukan pertanyaan ketika tidak mengerti penjelasan yang diberikan. Guru : “Okay class, we are going to have a quiz for today. I have divided you into two groups. Then I will give you two texts. The first text will belong to group one and the second will belong to group two. Then your job is to read the text and make questions based on it. The questions must include comprehension questions, vocabulary items and grammar items. The questions can be in the form of true/false, yes/no, matching to synonyms, antonyms and so on. You may use dictionary while making questions. Each member of the group has to contribute at least two questions. After having prepared the questions, you have to read the other half of the passage as you will have to answer questions based on it. Any questions so far?” ……….. It was to reduce students’ boredom during reading process. It also showed how the students understanding of narrative text delivered in the first meeting. 3. Observation and Reflection in the Field Stage This stage was coincided with the implementation stage. It was done by the researcher. The researcher observed the teaching learning process done by the teacher. She used field notes to take note about what happened in the class during the teaching learning process. Example 4. Descriptive Note Catatan Deskriptif: Guru melakukan apersepsi, ia menanyakan pada siswanya hal-hal seputar teks naratif. Guru : “Okay class, who knows what the narrative text is?” Siswa : “The text for entertaining the readers ma’am” (menjawab serentak) Guru : “That’s right. It is the text for entertaining its readers. What about the generic structure?” Siswa : “Orientation, complication, resolution ma’am”. (beberapa siswa) Hanya beberapa siswa yang mampu nenjawab pertanyaan dari guru mengenai generic structure dari teks naratif. Besides writing all the things happened, the researcher also reflected the data which they have gotten from the implementation stage. The result of the reflection was realized in the form of reflective data. Example 4. Reflective Note Catatan Reflektif: Guru melakukan apersepsi untuk Ejournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216 mengetahui sejauh mana siswnya telah memahami teks naratif. Hal ini dimaksudkan agar tidak terjadi pengulangan materi yang akan membuat siswa bosan. 4. Reflection It was the stage where the researcher and the teacher made a review of the data. They gave explanation of the data collected in the field notes. Then they analyzed the students’ feedback during the teaching learning process using appropriate material. This feedback was as the measurement of how the students’ comprehension. To measure the students’ comprehension, the researcher and the teacher had to make the criteria. They were set from the research questions of the study. If the students could accomplish all the criteria stated in the research questions, the cycle of the study was successful. From the first task, the researcher indicated that 75% of the numbers of the students have been able to categorize the text of Snow White based on its generic structure and make inferences while reading the text. The second task indicated that 75% of the numbers of the students have been able to identify the moral value of the texts, Mantu’s Little Elephants and The Goose That Laid Golden Eggs, ask questions of the texts as well as answer the questions. Those result indicated that the goals of the study have been accomplished. So the next cycle was not needed. Data Collection Technique The researcher was the key instrument of the study while data collection technique for this study was by using observation which was done in form of qualitative data. Wallace (1998) states qualitative is used to describe data which are amenable to be counted or measured in an objective war and are therefore “subjective”. Data will be presented in the form of words, phrases or sentences. Meanwhile, The aimed of qualitative approaches is to offer descriptions, interpretations and clarification of naturalistic social context. Qualitative research draws on the data collected by the researcher to make sense of the human behavior within the research context (Burns: 1999). The researcher used unstructured field notes to write all the information and also everything happened during the teaching and learning process. Still according to Wallace (1998) making field notes can prevent the researcher from trouble and confusion in presenting data caused by continuing to the next things. It helped her to organize the data before the data was being analized. The field notes organized into descriptive and reflective notes. Descriptive note contains of the description of what happens during the teaching and learning process (see Example 3), while reflective note was used to write what the researcher’s opinions and comments about all the activity in the teaching and learning process (see Example 4). Data Analysis As Susanto (2007) states in his book that data which the researcher gets from the observation using unstructured format is very plentiful, but not all the data are relevant with the requirement, they need to be classified and proceed systematically. The relevant data would be classified based on the research question of the study. After reducing un-relevant data, the researcher classified relevant data based on the research questions of the study. There were four research questions. The first was about students’ ability in categorizing a narrative text based on its generic structure. The second data was about the students’ ability in identifying the moral value of the narrative text. The third was about the students’ ability in answering the questions of the narrative text. The last was about the students’ ability in inferring the narrative text. RESULTS AND DISCUSSION The Teaching Process of a Reading Class Before conducting classroom observations, the researcher discussed with the teacher about the problems encountered during the previous learning process. After that the teacher gave the lesson plan used in the previous study. The researcher then examined all the data obtained from the description of the teacher and the previous lesson plan. After that she could conclude that the reason why students have difficulty in reading comprehension was due to materials using by the teacher too difficult. The text used was beyond the ability of her students. This resulted in many more students who were silent during the learning process. Moreover, some students spoke with their friends. They surrendered to read as bored and not interested in the text provided by the teacher. Even if there were students who were reading, they were dependent on a dictionary to find the meaning of difficult words. This was very time-consuming. As a result, the purpose of reading that was comprehension was not achieved properly. Based on the previous lesson, the researcher made the revised lesson plan. In her revised lesson plan the researcher chose the appropriate material based on the teacher’s description of her students ability. This was done to make the students did not feel difficult to comprehend the texts given. The researcher also reformulated more specific indicators based on the basic competence, adjusted the learning objectives to the indicators, and designed the learning activities which would encourage students to participate as well as do the process assessment correctly. Students’ activities focused on making the students to comprehend the text. In this study, the researcher made collaborative research with the teacher. The teacher was the one who taught in the reading class. The researcher observed the teaching learning process followed by the students and took field notes based on it. Adjusted Reading Materials for Reading Comprehension 7 According to the observation done by the researcher and data in the field notes, the researcher could say that the students were very interested in doing reading activities. They also had discussion with their couple friend as well as their classmate in a big group. The learning process generally was running concussively. Although there were some students who found difficulties, it did not disrupt the learning process in reading class. By doing group discussion, they could learn to work together with their friends. The smart students would help their friends who found difficulties. The role of teacher was also evident in the learning process. Although the students could learn independently, but the teacher kept her eyes on them when they had discussions. The questions that were not answered by group discussion then it will be answered by the teacher. The use of appropriate materials that were in the revised lesson plan greatly helped students in reading class. The Students’ Ability in Categorizing the Narrative Text Based on Its Generic Structure The reading activities which was followed by the students were based on the revised lesson plan (Appendix 2) made by the researcher. When preparing revised lesson plan, the researcher should consider the appropriate indicators to make students understood the text properly. This indicator would be used to replace the indicators used by the teacher in the previous lesson plan. Based on the basic competence the students would learn the narrative text, the important thing to do was to introduce the narrative text itself to the students. It made them able to know the generic structure of narrative text and categorize text given by its generic structure. The data of students' ability to categorize the narrative text based on its generic structure when they had discussion would be the answer for the first research question. In the beginning of the class, the students were busy with themselves. It was because they used the language laboratory for today’s lesson. They needed few time to go there and prepare themselves to get the lesson. After awhile they could pay attention to the teacher. Then the students were greeted by the teacher. (1) (1) Teacher Students Teacher Choirul Teacher Students Teacher Students Antok Teacher : : : : : : : : : : “Assalamu’alaikum Wr. Wb.”. “Wa’alaikummusalam Wr. Wb.” (In choir) “Ayo Choirul silahkan dipimpin untuk berdoa” “Before we start our lesson today, let’s pray together. Pray begin. (Praying together) Finish.” “Good morning students, how are you today?” “Good morning ma’am, I’m fine, thank you.” “Do you fasting?” “Yeees Ma’am” “Ma’am fasting?” “Of course Antok, I do. This greeting purposed to warn the students that the lesson would be started. The teacher also asked the students to pray first before starting the lesson. The teachers wanted to familiarize her students with good habits so that this habit would be instilled in students. After greeting, the teacher the students’ attendance list was checked by the teacher. Then they got the explanation about what they were going to do for the lesson that day. The teacher read the basic competence and the learning objective for them. It was purposed to ensure that all the students knew what they needed to achieve at the end of the study. However some students complained to the teacher because they got many things to study. (2) (2) T Mega Dini T : : : : “Okay class, this is our basic competence for the lesson today. Merespon makna dan langkah retorika dalam esai pendek sederhana secara akurat, lancar dan berterima yang berkaitan dengan lingkungan sekitar dalam teks berbentuk recount dan narrative. For today, we will learn about narrative text. After studying, you are expected to be able to recognize what narrative text is, identify the communicative purpose of narrative text, identify the generic structure of narrative text, identify the language features of narrative text and find all the information stated in the narrative text.” “Waduh ma’am, kok banyak banget yang harus dipelajari.” “Iya ma’am.” “Don’t worry students, we’ll do it slowly. You can ask question if you don’t understand. And remember, it is not as difficult as you think.” Brown (2000) stated that teachers should subdivide their techniques into pre-reading, during-reading, and after-reading phases. It could be seen in dialogue (2) that the teacher had divided her technique into pre-reading phase. In this phase, she tried to tell the students about what they were going to do. Then she introduced the topic for the lesson to the students that was about narrative text. There were so many indicators that had to be mastered by the students for the day. Some students complained. But teachers could calm them well. The teacher convinced the students that all these materials would not be a big problem because they would learn slowly. This made the students feel comfortable with the learning atmosphere in the classroom. After giving explanation about the basic competence and the learning objectives, the teacher gave apperception for the students related to the goal they wanted to achieve. (3) Ejournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216 (3) T S T S : : : : “Okay class, who knows what the narrative text is?” “The text for entertaining the readers ma’am” (In choir) “That’s right. It is the text for entertaining its readers. What about the generic structure?” “Orientation, complication, resolution ma’am”. (Some students) Dialogue (3) indicated that not all the students answered her question. It meant that not all the students knew about the generic structure of narrative text. They needed more explanation from the teacher about narrative text. Then the teacher showed the slides of narrative text. The slides explained about what the narrative text is, the generic structure of narrative text, the communicative purpose of narrative text, language features of narrative text as well as an example of narrative text. The example given was the story Malin Kundang. During the slide was showed, the teacher also gave questions to the students about what on the slide. (4) (4) T S T Mega T Dini T S T S T : : : : : : : : : : : “Okay students, pay attention to these slides please. Here, you can see that narrative text is the text for … “ “Entertaining the readers” (In choir) “Good students. So if you want to be entertained, you can read narrative text. What about its generic structure? Let’s go to the next slide. It consists of the first, orientation. It is about the opening paragraph where the characters of the story are introduced. The second is complication. It is the part where the problems in the story developed. The third or the last is resolution. What is resolution? Anyone knows what is it?” “Problemnya diselesaikan ma’am.” “Good Mega, Here in resolution, the problem of the story is solved.” “Kalo sad ending gimana ma’am?” “Good question Dini. Resolution of narrative text can be better or worse. If it is better, it will be happy ending. If it is worse, … “ “It will be sad ending ma’am.” (In choir) “Great students. Any questions so far?” “No Ma’am” “The next is about the Galuh Mega T S T Honi Yayank T Antok T : : : : : : : : : : communicative purpose of narrative text. It is used to amuse, entertain and to deal with an actual or vicarious experience in different ways. Now I have question for you students, how are the language features of narrative text?” “Pake ed ed Ma’am” “Was were Ma’am” “Is it right? Let’s check in this next slide. The language features of narrative text are using past tense. So Mega and Galuh are right. Yang pake ed sama was atau were. It is because the story happened in the past time. Another language feature is using pronoun. What is pronoun?” (Silent) “Kata ganti orang, such as I, we, she, he and it. Who can mention the example of narrative text?” “Cinderella Ma’am” “Malin Kundang” “Good, students. Okay, have you ever read the story of Malin Kundang?” “Pernah ma’am, yang anak durhaka itu kan ma’am?” “Yes, you’re right Antok. Malin Kundang is one of the examples of narrative text. You can see in the slide.” To make them more understand about narrative text, the teacher used the story which is common for them. According to Brown (2000), the teacher had to balance authenticity and readability in choosing texts. The teacher should adjust the text given to the abilities and needs of her students. By doing this, the students would be more interested to read a given text. The story used by the teacher is Malin Kundang. The students were interested to this story because they could use their knowledge to comprehend the text. Then each student accepted a copy of narrative text from the teacher. The teacher explained the generic structure of the narrative text based on the text given. It made the students can understand each part of generic structure of narrative text easily. The teacher tried to make her students reach the learning indicators. (5) (5) T Della T Untari : : : : “It is the text of Malin Kundang. I’ll give you the copies. Please spread it out, Della.” (Spreading to her friends) “Okay class, now look at the text you have got. Which one is the orientation?” “Paragraf one Ma’am” Adjusted Reading Materials for Reading Comprehension 9 T Untari T Jatra T Jatra T S T Clara T S : : : : : : : : : : : : “Good Untari. How can you say like that?” “Ehm anu Ma’am. Tokohnya muncul di situ. Perkenalan” “Great Untari. So in the first paragraph, the writer introduces the characters of the story, the setting and we can say it is introduction. What about the conflict? Who knows?” (Raising hand) “Yes Jatra” “Paragraf dua sampe yang sebelumnya paragraph terakhir Ma’am” “Good answer Jatra. And the resolution? Who knows?” (Raising hand) “Wow, many students raise their hands. Good. Okay Clara, what is the answer?” “Last paragraph Ma’am” “You are right Clara. I think all of you have understood about narrative text well. Give applause for us” (Clapping hands) The students were asked to make pair group. They got another narrative text. This time the text was Snow White. They were asked to categorize narrative text they got based on its generic structure. (6) (6) T S T Choirul T S T : : : : : : : “Okay students, please make a couple group. You may choose it by yourself. Do it now!” (Making a couple group) “Help me to spread it out, Choirul. A text for each group.” (Spreading the texts) “It is Snow White story. Your job is to categorize it based on the generic structure. You can work with your group. Any questions?” “No Ma’am” “Good, you can work it now” Dialogue (5) and (6) indicated that the teacher has taught her students using “SQ3R” sequence. According to Brown (2000) teacher should follow the “SQ3R” sequence in their teaching. It could be seen from the activities she used for teaching reading. Firstly the teacher explained about the generic structure of narrative text. She also gave several texts that were used to sharpen the students’ understanding of narrative text. The step of question was also used by the teacher. It was because from the question that the students asked and answered, the teacher could measure how far the students have understood the lesson. To make the students did not feel bored, the teacher asked students to create a group. In addition to that, this was done to make students able to work well together. Some students seemed to easily categorize the narrative text based on its generic structure, but some students still seemed difficult to do so. For this reason was why the teacher made the students work in groups. It was intended that the students could help each other. The students who already understood about narrative text could help their friends who still did not understand about it. (7) (7) Galuh Clara Galuh Clara Galuh Clara : : : : : : :Paragraf yang “She fled to the dungeon beneath the castle. There the Queen mixed a potion that would change her into an old hag. Then she took an apple and slowly dipped it into another potion sampai habis itu masuk complication ya?” “Iya, itu complicationnya.” “Bawahnya itu masa juga complication lagi Ra?” “Iyalah, kan dalam satu teks narrative bisa punya lebih dari satu complication.” “Ada 4 complication ya berarti? “ “Nah itu bener. Bisa loh sebenarnya kamu.” The dialogue (7) showed that a student tried to help another. They discussed what they did not know. Brown (2000) explained teachers should use techniques that are intrinsically motivating. Divided the students to work in groups was one of the ways in which the teacher could motivate her students. The students who were not able to comprehend the text well would be motivated by a friend who was able to comprehend the text well. This would impact on the learning outcomes of students which the students were able to understand the reading text properly. In the discussion, there were several groups that both members found difficulties in categorizing the generic structure of the text. It was because they have not really understood what has been explained by the teacher. The students who had difficulties ask the teacher for more explanation (8) (8) Yossia T Yossia T : : : : : “Ma’am, kalo dari orientation ke complication itu ada jedanya atau enggak” “What do you mean by Jeda?” “Itu loh Ma’am, kaya peralihan” “Orientation is the paragraph where the writer introduces the character, the setting etc. While complication is the paragraph where the conflict Ejournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216 Yossia T : : appears. So when you find a conflict in the paragraph you read, it means that it is complication. Is it clear?” “Oalaah gitu Ma’am. Oke Ma’am, understand” “Good” After all students were finished with their discussion, the teacher asked the students to discuss it together. What they have discussed with their groups. This was done in order that the students really understood about narrative text. Students seemed eager to discuss with the teacher. They wanted to show that they have mastered the material taught. (9) (9) T S T Dodi T S T : : : : : : : “Okay students, have you finished?” “Yes Ma’am” Great students. Now, we are going to discuss it. Okay Dodi, which one is the orientation?” Itu Ma’am, yang paragraf pertama. Yang long ago sampe was very cruel” “ Is it right students? “Yes, Ma’am “Okay class, go on to the next ……” (Continuing to the next discussion) At the end of the discussion session, the students seemed to understand about the generic structure of narrative text. It could be seen from the many students who had been able to categorize narrative texts provided by the teacher based on its generic structure. It was supported by dialogue (7), dialogue (8) and dialogue (9). The teacher did not have trouble when asking her students to discuss the generic structure of narrative text. When they still did not find the answer of their discussion, then the student might ask the teacher. It was which made the students able to properly categorize the narrative text. Then the teacher could continue to the next activities. The Students’ Ability in Identifying the Moral Value of the Narrative Text The second research question to be answered by the researcher was the ability of students in identifying the moral value of the narrative text. Based on the description of teachers when teaching reading using previous lesson plan, many students did not comprehend the narrative text delivered by the teacher, especially to identify the moral value of the narrative text itself. Then the researcher changed the narrative text given to students in the revised lesson plan. This was done to make students were able to comprehend the text better as well as able to identify the moral value of narrative text. Brown (2000) stated in his book that it needs the follow-up of the activities of reading they did. The teacher had to make a follow up activities after the students did reading activities. It will help her to know her students’ reading understanding of the text. What they have got of the text. Then the teacher re-explained the last material to assure that all students have understood the concept of narrative text well. Later, she went on to the next activities. Akgün (1997) did a study which concluded that the teacher must try to use fun activities in the classes before she makes the necessary changes according to the specific needs and attitudes of your own students. The fun activity which was used by the teacher was Quiz. The use of “Quiz” was adapted from Raman (2004). He said that the used of Quiz Game could motivate students to read and sustain their interest in reading. When reading became a game it took away the monotony that they appeared to associate with the act of engaging with the printed page. Then the teacher divided the students into two groups. It was a big group. The students then gathered with their group. It took a rather long time because some students did not get along with the group. There were some who did not join the group, but it could be overcome after the teacher warned them. (10) (10) T Choirul T Jatra T Jatra Aprianti T Jatra T S T Honi T Yuli : : : : : : : : : : : : : : : “Okay students, I will divide you into two group” (Demonstrating with hands) “Ma’am kelompoknya pilih sendiri atau dipilihkan?” “I’ve chosen the group for this quiz. The first group consists of the students who were in even numbers. The second group consists of the students who were in odd number… “ (Raising hand) “Ma’am” “Yes Jatra” “Even number itu apa Ma’am?” “Nomer genap ya Ma’am” “Yes, you’re right Aprianti. Even number means nomer genap, while odd number means nomer ganjil. Get it?” “Oalah. Ngobrol dong Ma’am kalo gitu maksudnya” “Now, all of you please gather with your group” (Noisy) “Ssssst, hayo Honi where is your group? Go go, get your group.” “Yes yes Ma’am” “Yuli, what are you doing? Stop talking get your group right now” “Yes Ma’am” (Walking to her group) Then the teacher explained how to do quiz to the students. (11) (11) T : “Okay class, we are going to have a quiz for today. I have Adjusted Reading Materials for Reading Comprehension 11 Laura T Laura T : : : : divided you into two groups. Then I will give you two texts. The first text will belong to group one and the second will belong to group two. Then your job is to read the text and make questions based on it. The questions must include comprehension questions, vocabulary items and grammar items. The questions can be in the form of true/false, yes/no, matching to synonyms, antonyms and so on. You may use dictionary while making questions. Each member of the group has to contribute at least two questions. After having prepared the questions, you have to read the other half of the passage as you will have to answer questions based on it. Any questions so far?” “Ma’am, what is comprehension question? “ “Comprehension question is a question which is related to the text. It can be explicit meaning which is written clearly in the passage such as characters in the story, or implicit meaning which is not written clearly in the passage such as main idea, moral value and so on.” “Oh, pelajaran yang bisa diambil dari cerita gitu ya Ma’am?” “You’re right Laura. Your time for reading and preparing the questions are only 15 minutes while for the next second text you have only 5 minutes. So your time is only 20 minutes for all” (Demonstrating with hands) Dialogue (10) and dialogue (11) indicated that the teacher played the role as a leader of the class. She was controlling her students before letting them worked with the group. Valette & Disick (1972) explained that reading involved internal behaviors. One of them was perception where the teacher introduced the language. In the dialogue 10, the teacher read the instruction for playing quiz. It was the teacher’s way to introduce to her students about the quiz. How they could play the quiz. In addition, the teacher also used a simple instruction that was easily understood by students. According to Brown (2000) teaching reading skill should be in an interactive curriculum, in which the teacher used quiz to teach reading. Besides, she always remembered to use simple instructions for her quiz. It was because she knew that her students were lack of vocabularies. If she used the complicated instruction, her students would not understand what she said. It meant nothing. The students then got a text of narrative. They read it carefully. Each team also seemed keen to make questions based on the text they read. They were quickly able to make the question of the text. This was because they have already known about the concept of narrative text. (12.1) & (12.2) Group 1 (12.1) Antok Okta Antok Fitri : : : : “Heh, kamu bikin pertanyaan apa?” (Looking at Okta’s question) “Ealah Tok, baca dong. Bikin apa kek” “Fit, tanya apa dong?” “Siapa tokohnya aja Tok, nggak papa” (Other members of group one were discussing) Group 2 (12.2) Wahyu Mega : : “Udah Meg?” “Udah. Heh kalian udah belum bikin pertanyaannya? Buruan, mau abis waktunya” (Other members of group two were discussing) After finished making question, they got another text from their opposite team. They read it more carefully because they would have questions about the text and had to answer it correctly. Then the teacher explained the rules of the game. The students could easily understand the teacher’s explanation because she used simple instructions. After knowing the rules, they looked more enthusiastic to play the quiz. During the quiz was held, many questions arose. Some questions could be easily answered, but there were some questions that needed more understanding. (13.1) & (13.2) Group 1 (13.1) Dina Dodi T Dina T Group2 : : : : : : “Why did the elephant screech?” “Because they heard the word snack” “Is it correct Dina the answer from Dodi?” “Correct Ma’am” “So, group 2 gets 1 point” “Yeeeeee” (In choir) Group 2 (13.2) Mega Okta T Mega : : : : “What is moral value of the story of the Goose that Laid Golden Eggs?” “Mmm, We should not be greedy” “Is it correct Mega the answer from Okta?” “Correct Ma’am” Ejournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216 T Group1 : : “So, group 1 gets 1 point” “Yeeeeee” (In choir) The dialogue above (13) showed that some students have been able to reach an understanding of the explicit message conveyed by the author. Taking from the results of the quiz, the teacher discussed with the students whether they still had difficulties or not. It was based on Brown (2000) statement, since reading was unobservable skill; the researcher indicated the students’ comprehension from how the students gave responses to their teacher. At first only a student who asked to the teacher, then another asked either. The students who asked showed that he had understood what was being taught by the teacher. Then the teacher gave explanation clearly about the questions. (14) (14) Dodi T Mega T Okta T Choirul T Untari T Mega T T + S : : : : : : : : : : : : : “Moral value itu apa?” “Good question Dodi. Moral value is the point of what we can take from the story. So you explain about what you get after you read that story. Is there any other questions?” Loh Ma’am kalo gitu tujuan penulisan itu apa Ma’am? Beda ya sama moral value?” “The purpose of writing is something which is conveyed by the writer to the reader. Whereas moral value is what the readers gain after reading/